VD_FINDINFO Décision / 2011 / 210 vom 22. Januar 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, PROLONGATION, EXPERTISE PSYCHOLOGIQUE | 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 CPP (CH)